Effectiveness of a virtual reality-based cognitive training program on memory, executive functioning, and processing speed in individuals with substance use disorders: a quasi-experimental study - Caetano, Tânia; Pinho, Maria Salomé; Ramadas, Eduardo; Freire-Santos, Filipa; Dixe, Maria dos Anjos (Frontiers in Behavioral Neuroscience, 2025)
BackgroundCognitive deficits are frequently observed in individuals with Substance use disorders (SUD) and have been linked to poorer treatment outcomes and a heightened risk of relapse. We aimed to study the effectiveness of a 6-week virtual reality-based cognitive training program (VRainSUD-VR) on neuropsychological outcomes, specifically memory, executive functioning, and processing speed, as well as on treatment dropout rates in individuals with SUD. We hypothesized that adding VRainSUD-VR to treatment as usual (TAU) would lead to greater cognitive improvements compared to TAU alone. As a secondary hypothesis, we expected VRainSUD-VR to reduce false memories relative to TAU.MethodsA non-randomized design with a control group, pre- and post-test assessments, and convenience sampling was employed. Patients (N = 47) were assigned to either the control group (CG), which received TAU (n = 22), or the experimental group (EG), which received VRainSUD-VR in addition to TAU (n = 25). Cognitive and treatment outcomes (e.g., dropout rates) were assessed at pre- and post-test.ResultsStatistically significant time × group interactions were found for overall executive functioning [F(1, 75) = 20.05, p < 0.001] and global memory [F(1, 75) = 36.42, p < 0.001], indicating the effectiveness of VRainSUD-VR. No significant time × group interactions were found for most processing speed outcomes (p > 0.05).ConclusionVRainSUD-VR could be integrated into residential programs to improve general executive functioning, perceptual reasoning, and working memory, including visual working memory, as well as different aspects of global memory, such as visual, auditory, immediate, and delayed recall. Future research should explore the long-term effects of this intervention and consider additional potential mediating factors to gain a deeper understanding of the mechanisms underlying its effectiveness.